ANALYSIS IMPLEMENTATION OF NATIONAL FINANCIAL INCLUSION STRATEGY CONNECTED WITH SHARIA FINANCIAL INCLUSION - munir nur komarudin; Nugraha Nugraha; Dikdik Harjadi; Fany Oktaviani (Indonesian Journal Of Business And Economics, 2019)
ABSTRACT          The purpose of this research is to know the effect of financial education, community property rights, intermediation facilities and financial distribution channels, financial services to the government sector and consumer protection to Islamic financial inclusions. The sampling technique useda random sampling method and thesample isobtained 100 respondents. The independent variables (x) include: financial education, communityproperty rights, intermediation facilities and financial distribution channels,financial services in the government sector and consumer protection. This research used a quantitative approach with descriptive and verification methods and methods ofdata analysis using multiple linear regression analysis.The result of this study indicate that the implementation a five pillars of SNKI (The national strategy of financial inclusion) has a positiveand significant impact on Islamic financial inclusion, it’s mean that if the implementation a five pillars of SNKI had increased automatically the Islamic financial inclusion would be increased. Key Words:         Financial Education, Community Property Rights, Intermediation Facilities and Financial Distribution Channels, Financial Services to the Government Sector Consumer Protection and Islamic Financial Inclusion